O032 Implementing a test and treat pathway for Mycoplasma genitalium in men with urethritis attending a GUM clinic. (30th June 2016) - Reynolds-Wright, John; Verrall, Fabienne; Hassan-Ibrahim, Mohammed; Soni, Suneeta
Abstract : Background/introduction: National guidelines recommend testing men with non-gonococcal urethritis(NGU) for Mycoplasma genitalium (MG) where testing is available. Recent studies have shown concerning levels of macrolide resistance and high rates of treatment failure with 1 g azithromycin. In response to this, we changed our standard treatment of NGU to doxycycline and implemented a test and treat pathway for MG in male NGU. Aim(s)/objectives: To determine the prevalence of MG and to measure clearance rates of infection post-treatment. Methods: From 1 st September 2015 first void urine samples from men with NGU were routinely tested for MG using the Fast Track Diagnostics™ urethritis PCR. Men with confirmed MG were given 5days azithromycin and offered test of cure at 4 weeks. Results: 304 men had NGU over 5months. Mean age 33.2 years, 64.5% heterosexual, 77.6% white ethnicity and 8.2% HIV-positive. Tests for MG were performed in 230/304 (76%). 16.5% (38/230) were MG positive compared with 22.5% chlamydia. 6 (15.8%) men with MG were co-infected with chlamydia and 1 (2.6%) had urethral gonorrhoea. 20/38 men with MG (52.6%) were given azithromycin 5days, 8/38 (21.1%) had azithromycin 1g stat. 7/38 (18.4%) re-tested positive at 4 weeks, 6 of whom had initially had azithromycin 5days. All were given moxifloxacin 400mg for either 7, 10 or 14 days. Discussion/conclusion: The high rates of MG found support routine testing in men with NGU. Despite appropriate treatment, some men returned with positive TOC suggestive of macrolide failure. This demonstrates a need for more widely available MG diagnostics with resistance testing in the UK and attention to antimicrobial stewardship so that NGU can be better managed.